2021
DOI: 10.3390/children8030182
|View full text |Cite
|
Sign up to set email alerts
|

Promote Selective Attention in 4th-Grade Students: Lessons Learned from a School-Based Intervention on Self-Regulation

Abstract: Academic success is a complex concept comprising not only good academic performance, but also the development of competencies and the accomplishment made by the ends of learning. Among the motivational and attentional variables likely to influence academic success, extant literature reports the relevance of developing self-regulation and attentional control to foster school success. Still, little is known about how to foster attentional control competencies through training on self-regulated learning strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The current study explored the perceived impact of the evidence-based "Yellow Trails and Tribulations" intervention conducted by class teachers in a disadvantaged elementary school neighborhood through a qualitative analysis of the implementers' and observers' session sheets and final reports. Prior studies majorly used quantitative methods to assess the impact of the intervention conducted by researchers [30,46,54] and then led by class teachers [49,55] for research purposes. Regardless of the implementer (i.e., researcher or trained teacher), those studies indicated that the participating students reported higher SRL skills at the end of the intervention than their counterparts [30,49,54], namely students from disadvantaged backgrounds [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study explored the perceived impact of the evidence-based "Yellow Trails and Tribulations" intervention conducted by class teachers in a disadvantaged elementary school neighborhood through a qualitative analysis of the implementers' and observers' session sheets and final reports. Prior studies majorly used quantitative methods to assess the impact of the intervention conducted by researchers [30,46,54] and then led by class teachers [49,55] for research purposes. Regardless of the implementer (i.e., researcher or trained teacher), those studies indicated that the participating students reported higher SRL skills at the end of the intervention than their counterparts [30,49,54], namely students from disadvantaged backgrounds [46].…”
Section: Discussionmentioning
confidence: 99%
“…This narrative based-intervention has been implemented by researchers for fourthgraders (including students from minority or low socio-economic backgrounds) living in urban or rural areas [30,[46][47][48][52][53][54]. The results showed positive and significant impacts of the intervention on (i) the participants' self-reported SRL competencies and self-efficacy beliefs [46,48,[52][53][54], (ii) the observational cognitive engagement components related to SRL such as asking for help and verbalizations related to the task planning [30], and (iii) attention control, which was assessed using a standardized test (impressively, at the end of the intervention, the experimental group scored at the level of 13/14 years old, while the control group scored at the level expected for their age group [54]). A particular highlight of the study conducted with students from low socio-economic backgrounds was that students presenting low and medium scores of SRL in the pre-test showed the highest gains in the post-test with high effect sizes [46].…”
Section: The "Yellow Trails and Tribulations" Narrative-based Interve...mentioning
confidence: 99%
“…Learning itself is accomplished when students have their motivational and attentional variables positively engaged with the didactic content, and competencies are developed accordingly and result in academic performance. (Pereira et al 2021. ) There is little information on how to learn to improve the attentional control of students.…”
Section: Attentional Control Biasmentioning
confidence: 99%
“…Learning pains are due to relatively weak internal authority, and it is well known that, indeed, teachers are aware of differences in the levels of students has long been a problem that needs to be addressed. (Pereira et al 2021. ) Many learners address a complex and diverse variety of diagnosed or latent ADHD, autism or anxiety disorders, etc.…”
Section: Attentional Control Biasmentioning
confidence: 99%
“…To learn class content and engage in class, students are expected to not only use a set of cognitive strategies (e.g., working memory or problem-solving strategies), but also to be able to focus their attention and inhibit disruptive behaviors, overcoming background constraints ( Fitzpatrick, 2012 ). The use of these strategies and skills as tools to attain goals involves self-regulation and the exercise of willful control over behavior ( Fitzpatrick, 2012 ; Archambault and Dupéré, 2017 ; Pereira et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%